2016
DOI: 10.1051/parasite/2016012
|View full text |Cite
|
Sign up to set email alerts
|

RecombinantToxoplasma gondiiphosphoglycerate mutase 2 confers protective immunity against toxoplasmosis in BALB/c mice

Abstract: Toxoplasmosis is one of the most widespread zoonoses worldwide. It has a high incidence and can result in severe disease in humans and livestock. Effective vaccines are needed to limit and prevent infection with Toxoplasma gondii. In this study, we evaluated the immuno-protective efficacy of a recombinant Toxoplasma gondii phosphoglycerate mutase 2 (rTgPGAM 2) against T. gondii infection in BALB/c mice. We report that the mice nasally immunised with rTgPGAM 2 displayed significantly higher levels of special Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 49 publications
2
10
0
11
Order By: Relevance
“…caninum ( Chen et al, 2016;Dellarupe et al, 2014a;Mordue et al, 2001;Nischik et al, 2001;Rodgers et al, 2005;Sibley et al, 2002;Tao et al, 2013;Wang et al, 2016).…”
Section: Evaluación De Los Niveles De Producción De Citoquinasunclassified
See 3 more Smart Citations
“…caninum ( Chen et al, 2016;Dellarupe et al, 2014a;Mordue et al, 2001;Nischik et al, 2001;Rodgers et al, 2005;Sibley et al, 2002;Tao et al, 2013;Wang et al, 2016).…”
Section: Evaluación De Los Niveles De Producción De Citoquinasunclassified
“…En modelo murino, la caracterización del perfil linfocitario se hace a partir de ensayos de linfoproliferación, en éstos se realiza el cultivo de células de bazo de ratones infectados y se procede a desafiarlos con antígeno de lisado total (TLA) de T. gondii. Habitualmente se utiliza la cepa RH para la producción del TLA ( Chen et al, 2016;Tao et al, 2013;Wang et al, 2016), pero algunos autores han propuesto desafiar los cultivos contra los mismos TLA con los que han sido inoculados los ratones (Rodgers et al, 2005). A continuación, se deben incubar los cultivos, los tiempos varían respecto a la IL que se desee buscar ( Chen et al, 2016;Tao et al, 2013;Wang et al, 2016).…”
Section: Evaluación De Los Niveles De Producción De Citoquinasunclassified
See 2 more Smart Citations
“…In a murine model using Swiss mice, the brain and the liver were the least infected organs after infection with RH strain and ME49 strain, respectively 16. Also, with the RH strain but using BALB/c mice, Wang et al observed higher parasite loads in the liver than in the brain 17. Juránková et al quantified Toxoplasma in different tissues from artificially infected goats (ingestion of oocysts)18 and showed that at 30 days postinfection (dpi), the liver was the least infected organ (50% of samples, with lowest parasite loads) but became one of the most infected ones at 90 dpi (100% of samples, fourth highest mean parasite load after lung, dorsal muscle and brain specimens).…”
Section: Discussionmentioning
confidence: 99%